Bâtisseuses de cathédrales ? - Sandrine Victor (Mélanges de la Casa de Velázquez, 2010)
Women appear in the accounts of building site managers at Gerona in the Late Middle Ages, particularly those of the church of San Feliu and the cathedral of Santa Maria. They discharged a variety of tasks, albeit they tended to work largely at low-skilled jobs. Although generally paid less than men, some did achieve a measure of parity in that respect. They often had family ties with a member of the Guild –wife, daughter, niece or sister– but some actually engaged in paid work independently, running a workshop or working on building sites where their husbands were not employed. However, they are only rarely mentioned in documentary sources, and the by-laws of the Guilds denied them the right to work as full professionals. Nonetheless, they played a key role in family strategies when it came to forging alliances that would benefit the professional activity of the future husband.